Author: personal – social – eternal (interpretive field of «Diary» by V. Vynnychenko) - Матвєєва, Тетяна Степанівна; Рудаченко, Аліса Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The diary papers of V. Vynnychenko (1911—1925) as a special interpretive field for studying the author’s world-view aesthetics and his creative intentions are analyzed. The text of the diary is systematized, based on the relevant material: the author’s thoughts on the nature of creativity as a special way of comprehending the world and a person in it; creativity as a manifestation of a person’s specific mental organization; creativity as an opportunity for self-manifestation in the present/future dyad; etc. The degree of correlation of conditions and possibilities to create, which were important for V. Vynnychenko as a politician while the fundamental changes at the beginning of the XXth century in Ukraine took place are also noticed in the article. The author’s issues given in the diary are considered in the aesthetic context of the literary process at the turn of the XIX-XXth centuries, when cardinal changes took place under the influence of interpretative changes of the world picture in philosophy and culture in general are represented in the given work. In addition, attention was paid to the concept of «creative act» and its understanding by V. Vynnychenko as a staged phenomenon: the plan, the stages of its realization, the role of intuition, fiction, fantasy in the creation of the another reality. The author’s interpretation of the author’s phenomenon taking into account to the interaction of the concepts of «endowment», «talent» and «genius» is given and commented. The emphasis is placed on V. Vynnychenko’s diary thoughts about the latest trends in Ukrainian literature of the early XXth century: homocentration, modernism as an art system renovation of the genre and poetic paradigm. To sum up, this allowed to understand the creative laboratory of the author more deeply and earnestly. The diary material is directed to the artistic creation of V. Vynnychenko - the play «The black Panther and the White Bear» for their semantic proximity: the process of creativity, psychological, aesthetic dominant of creativity, symbolism, artist’s essence researches. The perspective of the proposed direction of studying mnemonic and literary material is grounded, which allows the use of an interdisciplinary methodology for understanding aesthetic phenomena.